"From the same mad planet": a grounded theory of service users' accounts of the relationship within professional peer support. Issue 4 (12th December 2016) - Bailie, H. Alistair; Tickle, Anna; Rennoldson, Michael
Abstract : Purpose: Peer support (PS) workers are being employed despite uncertain evidence for clinical and cost-effectiveness. Psychological theories have been proposed to explain the mechanisms of PS but these lack empirical validation and specificity to professional PS. The purpose of this paper is to develop a substantive interpretive grounded theory of service-users' experience of professional PS work. Design/methodology/approach: Constructivist grounded theory was used throughout. Semi-structured interviews were conducted with ten service-users who had engaged with a professional PS worker. Findings: Three overarching themes were constructed. "The process of disclosure" describes how disclosure of mental health difficulties, experiences as a service-user and wider disclosure about life experiences, interests and values facilitate the development of a shared identity with the PS worker. "The product of disclosure" highlights the sense of being understood as a result of the disclosure and marks a deepening of the relationship. "Dual roles" describes the tenuous position of holding both a professional relationship and friendship. Research limitations/implications: Future research should seek to refine the theory developed and compare the effects of therapist self-disclosure with that found within PS. There were limitations within the study, including limited diversity within the sample as well as difficulties with recruitment. Originality/value: This study connects service-users' accounts of receiving PS with existing psychological theory to move towards an understanding of the relationship between receivers and providers of professional PS.